Kedekatan Cina-Jepang di Tengah Perang Dagang Cina-Amerika Serikat pada 2018-2019: Analisis Teori Complex Interdependence - Aini, Resi Qurrata (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2021)
This article explains why countries change their foreign policy from previously antagonistic to cooperative one focusing on the change in bilateral relationship between China and Japan amidst escalating trade wars between USA and China in 2018-2019. In doing so, it uses a qualitative method with a single case study approach. Relevant data were collected through literature study method from various official statements and documents of related countries. Using the theory of complex interdependence as its analytical framework, this article shows that amidst escalating trade wars between USA and China, China and Japan developed a closer bilateral relationship, especially in economic cooperation. Both countries benefitted a lot from these close bilateral ties. This was made possible because China-Japan realized that they experienced complex interdepency so that instead of conflict and antagonism, cooperation was the best policy for both countries.